(3QSGdI aj Mb Gdjbjf aj eYQaI CUhd GdOjf aj GdfHhIs
(3ChdgG (B:s
(3GdHGH GdKGdK ef Mb Gdjbjf ai eYQaI CUhd GdOjf ai GdfHhI hajgG aUhd aUd ai HjGf GdMceI ai HYKI GdCfHjGA s
(3BNQgG (B:s
(3ai fXQ Cgd GdfXQ cd hGMO ef GdCFeI GdCKfi YTQ eYLRg dNjQ GdHTQ Udi Gddg Ydjg hYdjge YOO GdThc hGdTLQ hGdTYQ hGdhHQ hGdbWQ hGdeWQ hGdUNQ hGdeOO s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B4s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd s
Keywords: (3GdeLGejYs